2017
DOI: 10.1186/s12902-017-0157-7
|View full text |Cite
|
Sign up to set email alerts
|

Corticomedullary mixed tumour resembling a small adrenal gland-involvement of cancer stem cells: case report

Abstract: BackgroundAdrenal corticomedullary mixed tumours are very rare. Its mechanism is rarely reported. Here we report the first case of a corticomedullary mixed tumour resembling a “small adrenal gland” with distinct arrangement of the cortical and medullary layers. We further hypothesize regarding the tumorigenic mechanism of this tumour.Case presentationA 58-year man had been diagnosed with diabetes and hypertension for 3 years. His 24-h urine vanillylmandelic acid (VMA) levels were slightly elevated. An abnormal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Furthermore, during pregnancy, the placenta is a source of ACTH and CRH, which exaggerates the circulating ACTH levels synergistically with ACTH induced by hyper catecholamine and may result in the proliferation of the cortical components within the pheochromocytomas. Another hypothesis is that tumor stem cells may contribute to the development of these 2 distinct tumor cells [ 5 ]. In the current study, whole exome analysis revealed the FGFR4 -G388R variant as a possible pathogenic gene alteration, and p-S727 STAT3, a downstream signal of the FGFR4 -G388R variant, was observed mainly in the adrenocortical adenoma component, suggesting that the FGFR4 -G388R variant and downstream signaling may play a role in the development of adrenocortical adenoma components.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, during pregnancy, the placenta is a source of ACTH and CRH, which exaggerates the circulating ACTH levels synergistically with ACTH induced by hyper catecholamine and may result in the proliferation of the cortical components within the pheochromocytomas. Another hypothesis is that tumor stem cells may contribute to the development of these 2 distinct tumor cells [ 5 ]. In the current study, whole exome analysis revealed the FGFR4 -G388R variant as a possible pathogenic gene alteration, and p-S727 STAT3, a downstream signal of the FGFR4 -G388R variant, was observed mainly in the adrenocortical adenoma component, suggesting that the FGFR4 -G388R variant and downstream signaling may play a role in the development of adrenocortical adenoma components.…”
Section: Discussionmentioning
confidence: 99%
“…Mixed corticomedullary adrenal tumors (MCATs) are very rare and present as a single heterogeneous mass composed of intimately admixed adrenocortical and medullary cells [1][2][3][4][5][6][7][8][9]. e medullary component usually consists of pheochromocytes, whereas the cortical component is usually an adrenocortical adenoma or less frequently an adrenocortical carcinoma [1][2][3][4][5][6][7][8][9]. Clinical and/or biochemical evidence of cortisol hypersecretion, putatively by the cortical component, has been documented in about half of the reported cases of mixed corticomedullary adrenal tumors [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…e medullary component usually consists of pheochromocytes, whereas the cortical component is usually an adrenocortical adenoma or less frequently an adrenocortical carcinoma [1][2][3][4][5][6][7][8][9]. Clinical and/or biochemical evidence of cortisol hypersecretion, putatively by the cortical component, has been documented in about half of the reported cases of mixed corticomedullary adrenal tumors [1][2][3][4][5][6][7][8][9]. ese tumors are especially rare in young patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixed corticomedullary tumors (MCMTs) are composed of medullary and cortical cells in a single adrenal tumor [ 1 ], which can produce catecholamines, cortisol, or both [ 2 ]. MCMTs are extremely rare because the adrenal medulla and cortex have different embryological origins, namely, the neuroectoderm and mesoderm, respectively.…”
mentioning
confidence: 99%